6s-54=-12

Simple and best practice solution for 6s-54=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6s-54=-12 equation:


Simplifying
6s + -54 = -12

Reorder the terms:
-54 + 6s = -12

Solving
-54 + 6s = -12

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + 6s = -12 + 54

Combine like terms: -54 + 54 = 0
0 + 6s = -12 + 54
6s = -12 + 54

Combine like terms: -12 + 54 = 42
6s = 42

Divide each side by '6'.
s = 7

Simplifying
s = 7

See similar equations:

| (4/x)+(3/7x^2)=0 | | (4/x)+(3/7x^2) | | -36=6w+30 | | 5-(6x+3)=14-8x | | -16t^2+25t+3=0 | | 4b^2-4b+1=0 | | 9u-54=45 | | 5+(y/8)=-3 | | 9x-(7x-5)=21 | | 3(t-3)+5(t+3)=32 | | 28-7a=-49 | | h(t)=-16t^2+32t+300 | | 2.5(7x+3)+4+5=2.5(7x+3)+4+5 | | 49=-(4x-17) | | -x^2-0.5x+7.5=0 | | -21+3b=-24 | | -8n-4=-2+n-6-8 | | x+3-x-2= | | 56=7-7r | | 13=(g/3)+4 | | 18y^2-12y=0 | | 2/3(9x-12x+6) | | -5r+10=-5 | | y=-16x^2-8x+120 | | 18y^2-12y=0 | | 15=-24+3s | | 8+3y=7x | | 3x+7=5x+9 | | x-12=-2x+6 | | 3/(t+3)-1/t-5/(2t+6) | | -2(7n-8)=-96 | | 6x-24=54 |

Equations solver categories